Sport science college students and career stress - Yasar, Onur Mutlu; Turgut, Murat (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2019)
The aim of this study is to examine the career stress levels of university students in different faculties according to age, gender, faculty, class and financial status variables. The research was conducted using a quantitative research design. The sample of this study consisted of 1,189 university students from Kastamonu University Education Faculty, School of Physical Education and Sports, Faculty of Arts and Faculty of Engineering and Architecture. Career Stress Scale consisting of 20 items and three sub-dimensions was used. Data were normally distributed and parametric analysis was used. According to the findings of this study, it was determined that the average score of the participants was 2.43 from the total score of the career stress scale. In this context, it was found that the career stress levels of the participants were moderate at the lower limit. According to the average scores of the participants, the lowest subscale was found to be an external conflict with 2.13 average and the highest subscale was found to be job anxiety with an average score of 2.82. A significant difference was found almost between all different groups in different ways (p > 0.05). As a result, it was found that the career stress levels of the university students participating in the research were moderate, as well as differences according to variables such as gender, class, age, faculty and income status. Among these differences, the most striking ones appear to be the variables of age and income. In this context, it was determined that university students who have lower age and lower-income status level have higher career stress level than age and income status variables. Keywords: Career, collage, stress, sport, students, university.
Keywords: 4. Education; 16. Peace & justice